2014
DOI: 10.1093/sw/swu043
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of Veterans with "Invisible" Injuries: What We Know and Implications for Social Work Practice

Abstract: Today, as a result of the longest volunteer-fought conflict in U.S. history, there are many wounded coming home not only with posttraumatic stress disorder (PTSD), but also with traumatic brain injury (TBI), which together have been called the "signature" or "invisible" injuries of the Iraq and Afghanistan wars. Caregivers are an important part of their recovery, yet little is known about them, as previous research on caregivers mostly focused on geriatric populations. According to one estimate 275,000 to 1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 37 publications
0
33
1
1
Order By: Relevance
“…It is worth noting that our statistical analysis did not see a significant difference between the male and female military caregivers. This is not consistent with previous findings that female caregivers report more stress as a result of caregiving than male caregivers (National Alliance for Caregiving, ; Patel, ). The major reason for this inconsistency, we believe, is that among the initial 370 participant military caregivers, 352 (96%) were female caregivers and only 15 (4%) were male.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that our statistical analysis did not see a significant difference between the male and female military caregivers. This is not consistent with previous findings that female caregivers report more stress as a result of caregiving than male caregivers (National Alliance for Caregiving, ; Patel, ). The major reason for this inconsistency, we believe, is that among the initial 370 participant military caregivers, 352 (96%) were female caregivers and only 15 (4%) were male.…”
Section: Discussioncontrasting
confidence: 99%
“…Children of deployed veteran and service members may have increased anxiety that persists after the deployed parent returns home (Lester et al., ). Generally, female caregivers report more stress and experience greater morbidity as a result of caregiving than male caregivers (National Alliance for Caregiving, ; Patel, ). The wives or partners of veterans with PTSD are particularly likely to have symptoms of secondary traumatic stress and health issues (Dekel, Goldblatt, Keidar, Solomon, & Polliack, ; Dirkzwager, Bramsen, Ader, & Ploeg, ; Franciskovic et al., ; Yambo et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While male MFCGs were not excluded from the study, few elected to participate. Although male caregivers represent a smaller portion of MFCGs (approximately 4%), they experience similar challenges as caregivers and, based on other research, can benefit from interventions (Harris, ; National Alliance for Caregiving, ; Patel, ). Future research should include male MFCGs and analyses of data by gender (Houde, ).…”
Section: Discussionmentioning
confidence: 99%
“…The need for family members to suddenly take on the job of caring for their loved ones injured in service has become a mounting concern and problem across America. An even more growing interest has been that these individuals have been tasked to take on responsibilities to provide care for an injured service member or veteran, after notification of a loved one's injury during military service (Patel, 2015;Ramchand et al, 2014;Van Houtven, Oddone, & Weinberger, 2010;Zernial, 2015). Researchers have reported that in the United States of America, 5.5 million family caregivers provided care to those who served (Ramchand et al, 2014).…”
mentioning
confidence: 99%